The Relationship Between Genetic Factors and the Incidence of Fever Seizures in Children at Bhayangkara Setukpa Hospital Lemdiklat Polri Sukabumi City Year 2022 - Reni Anggraeni; Rita Putri Wati; Panduwita; Dhiny Isma (International Journal of Scientific Multidisciplinary Research, 2023)
Febrile seizures can be caused by various factors, genetic factors or a family history of seizures, an immature brain, and infection, so the cause of febrile seizures is called multifactorial. (Veisani Y. 2013). One of the factors, namely genetic factors, has a major influence on the incidence of febrile seizures. Based on previous studies, one-third of all febrile seizure patients have a history of seizures in their families. ObjectiveThis study aims to determine the relationship between genetic factors and the incidence of febrile seizures in children at Bhayangkara Setukpa Hospital, Sukabumi Police Education and Training Center, in 2022